Molecular beacon probes–base multiplex NASBA Real-time for detection of HIV-1 and HCV - Mohammadi-Yeganeh, S (Tehran University of Medical Sciences, 2012)
BACKGROUND AND OBJECTIVES: Developed in 1991, nucleic acid sequence-based amplification (NASBA) has been introduced as a rapid molecular diagnostic technique, where it has been shown to give quicker results than PCR, and it can also be more sensitive. This paper describes the development of a molecular beacon-based multiplex NASBA assay for simultaneous detection of HIV-1 and HCV in plasma samples. MATERIALS AND METHODS: A well-conserved region in the HIV-1 pol gene and 5’-NCR of HCV genome were used for primers and molecular beacon design. The performance features of HCV/HIV-1 multiplex NASBA assay including analytical sensitivity and specificity, clinical sensitivity and clinical specificity were evaluated. RESULTS: The analysis of scalar concentrations of the samples indicated that the limit of quantification of the assay was <1000 copies/ml for HIV-1 and <500 copies/ml for HCV with 95% confidence interval. Multiplex NASBA assay showed a 98% sensitivity and 100% specificity. The analytical specificity study with BLAST software demonstrated that the primers do not attach to any other sequences except for that of HIV-1 or HCV. The primers and molecular beacon probes detected all HCV genotypes and all major variants of HIV-1. CONCLUSION: This method may represent a relatively inexpensive isothermal method for detection of HIV-1/HCV co-infection in monitoring of patients.